An empirical investigation into the determinants of external debt in Asian developing and transitioning economies. Issue 1 (1st January 2021) - Dawood, Muhammad; Baidoo, Samuel Tawiah; Shah, Syed Mehmood Raza
ABSTRACT: This paper investigates the determinants of external debt in 32 Asian developing and transitioning economies for the period 1995–2019. Estimation is carried out using the generalized method of moments (GMM), which is capable of dealing with potential endogeneity problems. The results show that in both the short- and long-run, economic growth and investment reduce external debt, whereas exchange rate, trade, and government expenditure increase external debt. Diagnostic tests confirm the reliability and consistency of our findings, which should be taken into account by policymakers for policy formulation and implementation. Based on our empirical findings, relevant policy implications, aimed at reducing external debt in the selected Asian developing and transitioning economies, are provided for policy consideration.